Scar Effects of Unemployment: An Assessment of Institutional Complementarities - Gangl, Markus (American Sociological Review, 2006)
This article uses panel data from the Survey of Income and Program Participation (SIPP) and the European Community Household Panel (ECHP) for a comparative analysis of workers' post-unemployment earnings trajectories in the United States and 12 Western European countries. Across the study sample of industrialized countries, results of difference-in-difference propensity score matching show post-unemployment earnings losses to be largely permanent and particularly significant for high-wage and older workers as well as for women. The analyses also show that negative effects of unemployment on workers' subsequent earnings are mitigated through either generous unemployment benefit systems or strict labor market regulation. These effects stem partly from favorable behavioral responses that prevent downward occupational and industrial mobility and partly from changes in the overall structure of labor markets favoring the transferability of worker skills between jobs. These positive effects materialize despite the fact that labor market policies tend to successfully protect the core work force from experiencing a job loss in the first place.